Globalization: an inexorable phenomenal force - Michael Uzomah; Paul Olorunsola Folorunso (Center for Humanities and Innovation Studies, 2020)
Globalization is a wide-ranging universal influence on humanity’s existence, experience, and intercourse, as it is tending towards reducing the world into a singularized society. In the presence of this omnipresent phenomenon, the physical barriers between nations are illusive because communicative technologies, which are the driving force of globalization, know no physical barriers. It enables trans-border interactions in whatever aspect of the lives of nations possible in real time. The questions that are often raised when discourse on globalization feature at the local and international scene are: what is the nature and essence of globalization? Is the phenomenon of globalization establishing symbiotic political and economic relationships between nations? Or is the globalization a neocolonialism and western imperialism and hegemony? Is globalization not creating a new form of imbalanced dependencies between “the haves and the have not”? There are two contrary views regarding the significance of globalization to nation-states. The first view regards globalization as positive and ultimate, while the second perceives it as bad and needs reformation. Another question that also features prominently in discourse on globalization is, is it possible for a country to refuse to join the bandwagon of globalization? In response to this question, the paper maintains that an integrated understanding of globalization is an inexorable unifying phenomenon and mega shift-powered innovative digital technology that is continually plummeting the world’s landscape into a micro-space. This inexorable unifying phenomenon inevitably makes the experience and concern of a people and geographical space the general experience and concern of all people and geographical spaces in no time. The paper concludes that countries' prosperity in the global arena lies with how much they can forcibly assert themselves into the global scene, either as giants or as paupers or beggars or complainants.